2009
DOI: 10.1590/s0034-72802009000600005
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome do bloqueio capsular precoce relato de caso e especulação sobre o tamanho da parte óptica da lente como fator de risco

Abstract: INTRODUÇÃOA síndrome do bloqueio capsular é uma complicação da cirurgia de catarata que surgiu após a introdução da capsulorrexe (1) . Pode ocorrer no per-operatório, pós-operatório precoce ou tardio, com múltiplas etiologias propostas (2,3) . Na forma per-operatória o núcleo do cristalino bloqueia a capsulorrexe durante a manobra de hidrodissecção, podendo levar a ruptura da cápsula posterior (2) . Nas formas pós-operatórias, tanto na precoce como na tardia é possível o bloqueio se dá através do contato en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Kim et al (15) observed six cases in 206 cases (2.9%) with this IOL, while with other IOLs, according to various authors, the frequency ranges from 0.3 to 1.6% (1,10,15,21,22) . Marback et al (16) reported an even lower prevalence of 0.02%.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Kim et al (15) observed six cases in 206 cases (2.9%) with this IOL, while with other IOLs, according to various authors, the frequency ranges from 0.3 to 1.6% (1,10,15,21,22) . Marback et al (16) reported an even lower prevalence of 0.02%.…”
Section: Discussionmentioning
confidence: 91%
“…(8) For the early type, Kim et al (15) reported that increased axial length is a risk factor, mentioning a diameter greater than 25 mm. Although these cases have been reported with different lens types (1,2,6,15,16,20) , the early type is more common in lenses with flexible haptics, as they are more easily pushed forward. (5) In particular, the condition has been associated with a specific type of IOL, the Akreus Adapt by Bausch & Lomb.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations